A preliminary study on predictors of treatment response to repetitive transcranial magnetic stimulation in patients with treatment‐resistant depression in Japan. Issue 4 (30th August 2022) - Ikawa, Haruki; Tochigi, Mamoru; Noda, Yoshihiro; Oba, Hiroshi; Kaminaga, Tatsuro; Sakurai, Keita; Ikebuchi, Emi; Hayashi, Naoki; Kunugi, Hiroshi
Abstract: Background: Brain imaging studies have reported that the effect of repetitive transcranial magnetic stimulation (rTMS) is associated with the activities of the dorsolateral prefrontal cortex (DLPFC) and ventral medial prefrontal cortex (VMPFC). However, few studies have been conducted in Japanese patients. Aim: We aimed to identify brain regions associated with depressive symptom changes by measuring regional cerebral blood flow (rCBF) in the DLPFC and VMPFC before and after the high‐frequency rTMS to the left DLPFC in Japanese patients with treatment‐resistant depression. Method: Fourteen patients participated in the rTMS study and were assessed with the 17‐item Hamilton depression rating scale (HAM‐D17 ). Among them, 13 participants underwent magnetic resonance imaging scan of the brain using the arterial spin labeling method. The rCBF was calculated using the fine stereotactic region of interest template (FineSRT) program for automated analysis. We focused on eight regions reported in previous studies. Results: Depression severity significantly decreased after 2 week (HAM‐D17 :11.4 ± 2.8, P = 0.00027) and 4 week (HAM‐D17 : 11.0 ± 3.7, P = 0.0023) of rTMS treatment. There was no significant change in rCBF at each region in the pre‐post design. However, there was a significantly negative correlation between baseline rCBF in the right DLPFC and the improvement in HAM‐D17 score ( r = −0.559, P = 0.047). Conclusion: We obtained supportive evidence for the effectiveness of rTMS to the prefrontal cortex in treatment‐resistant depression, which may be associated with reduced rCBF of the right DLPFC before initiation of rTMS.